Challenges and Opportunities in Promoting Sustainable Organic Farming in India through Policy and Technical Interventions at FPO level - A case Study from Haryana - Kumari, Sunila; Kashyap, Poonam; N. Ravisankar (Journal of Agricultural Extension Management, 2022)
Owing to the nutritional and health benefits, positive impact on environmental and socioeconomic status of organic food, the annual growth rate of organic farming worldwide has been about 20 per cent for the last decade (Flávia et.al. 2020). Although India hosts the second largest number of certified organic farms (44,926) yet, due to 82 per cent of the Indian farmers being small and marginal (FAO), which creates challenges in their sustainability, it couldn’t yet contribute significantly to global organic food production. To address these challenges, the FPO seems to be a potential tool and further empowered with the adoption of organic farming systems it can address human as well as soil health and environmental issues. Despite interventions from the Government and other relevant bodies, the predicted success couldn’t be achieved, especially among FPOs having the main objective of organic farming. The current study was conducted among the FPOs of Haryana state, having organic farming as their major objective, to identify the pain points; areas of intervention and to formulate solutions to help them achieve their goals.